Diffusion in thorium carbide: A first-principles study - Perez Daroca, Diego Raul (2015)
The prediction of the behavior of Th compounds under irradiation is an important issue for the upcoming Generation-IV nuclear reactors. The study of self-diffusion and hetero-diffusion is a central key to fulfill this goal. As a first approach, we obtained, by means of first-principles methods, migration and activation energies of Th and C atoms self-diffusion and diffusion of He atoms in ThC. We also calculate diffusion coefficients as a function of temperature.